1996
DOI: 10.1093/hmg/5.6.783
|View full text |Cite
|
Sign up to set email alerts
|

Genomic imprinting of human p57KIP2 and its reduced expression in Wilms' tumors

Abstract: p57KIP2 is a potent tight-binding inhibitor of several G1 cyclin complexes, and is a negative regulator of cell proliferation. The gene encoding human p57KIP2 is located on chromosome 11p15.5, a region implicated in both sporadic cancers and Beckwith-Wiedemann syndrome (BWS), a cancer syndrome, making it a tumor suppressor candidate. Several types of childhood tumors including Wilms' tumor, adrenocortical carcinoma and rhabdomyosarcoma display a specific loss of maternal 11p15 alleles, suggesting that genomic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
73
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(73 citation statements)
references
References 28 publications
0
73
0
Order By: Relevance
“…7 Taken together, these observations suggest that that p57 Kip2 exerts tissue-specific effects during development. Interestingly during adulthood, it has also been reported that p57 Kip2 expression is reduced in various tumors, [8][9][10][11][12][20][21][22][23][24] suggesting a possible function for this protein in tumorigenesis. Importantly, decreased p57 Kip2 expression may provide an important prognostic implication for patients with ovarian, hepatocellular and colorectal cancers, and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…7 Taken together, these observations suggest that that p57 Kip2 exerts tissue-specific effects during development. Interestingly during adulthood, it has also been reported that p57 Kip2 expression is reduced in various tumors, [8][9][10][11][12][20][21][22][23][24] suggesting a possible function for this protein in tumorigenesis. Importantly, decreased p57 Kip2 expression may provide an important prognostic implication for patients with ovarian, hepatocellular and colorectal cancers, and acute lymphoblastic leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…Although IGF2, H19, SNRPN and p57 ~P2 (Hatada et al, 1996a) were confirmed to be imprinted as are their mouse homologs, INS has been shown to be expressed biallelically. Searching around the SNRPN region identified 4 novel imprinted genes, ZNF127, PAR5, PAR1 and IPW (Sutcliffe et al, 1994;Wevrick et al, 1994), all expressing paternally.…”
Section: Identification Of Imprinted Genesmentioning
confidence: 98%
“…Nine imprinted genes have been identified in man: the insulin-like growth factor II gene (tGF2) (Ohlsson et a/., 1993;Giannoukakis et al, 1993) and its receptor gene (IGF2R) (Xu et al, 1993), H19 gene (H19) (Zang and Tycko, 1992), the p57 K~P2 gene (Hatada et al, 1996), the Wilms tumor suppressor gene (WT1) (Jinno et al, 1994), the small nuclear ribonucleoprotein-associated polypeptide N gene (SNRPN) (Oz~elik et al, 1993), and transcripts (IPW, PAR1 and PAR5) from the Prader-Willi syndrome critical region (Wevrick et al, 1994;Sutcliffe et al, 1994). Among them, IGF2, SNRPN, IPW, PARI and PAR5 are paternally expressed, and the remaining 3 are maternally expressed genes.…”
Section: Introductionmentioning
confidence: 99%